2009
DOI: 10.1007/s11999-008-0700-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Disease-specific Instrument for Idiopathic Clubfoot Outcome

Abstract: In 2001, Roye et al. developed a disease-specific instrument (DSI) to measure outcomes of treatment for clubfoot. We assessed this instrument using a cohort of 62 patients, ages 5 through 12 years (mean, 8.6 years), with idiopathic clubfoot who were treated as infants by various methods. Treatment groups were defined by whether the patient received joint-invasive surgery (posterior or posteromedial release surgery) or joint-sparing treatment only (manipulation and casting with or without tendo-Achilles lengthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 18 publications
4
37
0
3
Order By: Relevance
“…The DSI score was introduced by Roye et al [17] and was validated by Dietz et al [20]. The latter [20] compared the DSI of 62 clubfoot patients after joint-invasive surgery and joint-sparing treatment at an age between five and 12 years. They reported a DSI score of 75 points for the joint-invasive group and 85.1 points for the joint-sparing treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…The DSI score was introduced by Roye et al [17] and was validated by Dietz et al [20]. The latter [20] compared the DSI of 62 clubfoot patients after joint-invasive surgery and joint-sparing treatment at an age between five and 12 years. They reported a DSI score of 75 points for the joint-invasive group and 85.1 points for the joint-sparing treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…We found that children awaiting tibialis anterior tendon transfer had worse function and satisfaction than children not undergoing tibialis anterior tendon transfer surgery. Dietz et al [3] reported that children who previously underwent joint-sparing surgery had better disease-specific instrument outcomes than children who underwent joint invasive surgery. Total disease-specific instrument scores of the tibialis anterior tendon transfer group at 12-month followup were similar to those of the joint-sparing surgery group reported by Dietz et al (p = 0.379).…”
Section: Discussionmentioning
confidence: 99%
“…Function and satisfaction were assessed using the diseasespecific instrument for clubfoot questionnaire [3,22], and quality of life was assessed using the Infant Toddler Quality of Life Questionnaire TM (www.healthact.com/itqol.php) [18].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Clubfoot deformity can be unilateral or bilateral (Barry, 2005) Research conducted in the United State shows that the prevalence of clubfoot varies between 0.64 and 6.8 per 1000 live births worldwide (Baker, Chesney, Miedzybrodzka & Maffuli, 2003) while a study by Dietz, Tyler and Leary (2009) …”
Section: Introductionmentioning
confidence: 99%
“…Surgical intervention involves posterior release and posterolateral and posteromedial release (Dietz et al, 2009) while conservative management involves manipulation and casting serial (Ponseti et al, 2009). Surgical intervention is best suited for late diagnosis and complex clubfoot (Sureh, Ahmed & Sharma, 2003) while conservative method is advocated as the first line of treatment for early intervention Morcuende et al, 2004).…”
mentioning
confidence: 99%